Constraining primordial black holes as dark matter using the global 21-cm signal with X-ray heating and excess radio background. Issue 3 (1st March 2022) - Mittal, Shikhar; Ray, Anupam; Kulkarni, Girish; Dasgupta, Basudeb
Abstract: Using the global 21-cm signal measurement by the EDGES collaboration, we derive constraints on the fraction of the dark matter that is in the form of primordial black holes (PBHs) with masses in the range 10 15 –10 17 g. Improving upon previous analyses, we consider the effect of the X-ray heating of the intergalactic medium on these constraints, and also use the full shape of the 21-cm absorption feature in our inference. In order to account for the anomalously deep absorption amplitude, we also consider an excess radio background motivated by LWA1 and ARCADE2 observations. Because the heating rate induced by PBH evaporation evolves slowly, the data favour a scenario in which PBH-induced heating is accompanied by X-ray heating. Also, for the same reason, using the full measurement across the EDGES observation band yields much stronger constraints on PBHs than just the redshift of absorption. We find that 21-cm observations exclude f PBH ≳ 10 -9.7 at 95% CL for M PBH = 10 15 g. This limit weakens approximately as M 4 PBH towards higher masses, thus providing the strongest constraints on ultralight evaporating PBHs as dark matter over the entire mass range 10 15 –10 17 g. Under the assumption of a simple spherical gravitational collapse based on the Press-Schechter formalism, we also derive bounds on the curvature power spectrum at extremely small scales ( k ∼ 10 15 Mpc -1 ). This highlights the usefulness of global 21-cm measurements, including non-detections, across wide frequency bands for probing exotic physical processes.